2013
DOI: 10.1371/journal.pone.0063465
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Induces Endoplasmic Store Ca2+-Dependent Inflammatory Responses in Lung Microvessels

Abstract: The pulmonary microvasculature plays a critical role in endotoxin-induced acute lung injury. However, the relevant signaling remain unclear. Specifically the role of endothelial Ca2+ in the induction of endotoxin-mediated responses in lung microvessels remains undefined. Toward elucidating this, we used the isolated blood-perfused rat lung preparation. We loaded microvessels with the Ca2+ indicator, Fura 2 AM and then determined Ca2+ responses to infusions of lipopolysaccharide (LPS) into the microvessels. LPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 53 publications
1
34
1
Order By: Relevance
“…Previous studies have reported that LPS perturbs intracellular Ca 2+ homeostasis in microglial cells, cardiomyocytes, and lung microvessels (Choi et al 2002;Beck et al 2008;Wang et al 2009;Kandasamy et al 2013;Magi et al 2015). In contrast, the present study showed that human sperm [Ca 2+ ] i was unaffected by LPS (Fig.…”
Section: +contrasting
confidence: 78%
See 2 more Smart Citations
“…Previous studies have reported that LPS perturbs intracellular Ca 2+ homeostasis in microglial cells, cardiomyocytes, and lung microvessels (Choi et al 2002;Beck et al 2008;Wang et al 2009;Kandasamy et al 2013;Magi et al 2015). In contrast, the present study showed that human sperm [Ca 2+ ] i was unaffected by LPS (Fig.…”
Section: +contrasting
confidence: 78%
“…5C, D). This discrepancy may be attributed to two factors: first, LPS changes [Ca 2+ ] i by regulating the expression of genes encoding Ca 2+ and Na + /Ca 2+ channels in microglial cells, cardiomyocytes, and lung microvessels (Choi et al 2002;Beck et al 2008;Wang et al 2009;Kandasamy et al 2013;Magi et al 2015). However, sperm lack active transcriptional machinery so that LPS could not affect intracellular Ca 2+ homeostasis by regulating gene expression.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial endotoxin (LPS) can directly induce Ca 2ϩ overload in ECs to cause endothelial barrier dysfunction and vascular injury (11,12). Bacterial cell wall component LPS ligates TLR4 to induce the expression of cytokines, chemokines, adhesion molecules, apoptotic factors, and several other mediators through NF-B and p38 MAPK activation (13)(14)(15).…”
mentioning
confidence: 99%
“…Because these events occur to a greater extent in BECs than at other locations of the pulmonary capillary bed, the lung’s immune response initiates with leukocyte accumulation at postcapillary branch points (19). Recent RFI studies on lung capillaries indicate that the endotoxin-induced expression of the leukocyte adhesion receptor ICAM-1 also occurs as a consequence of IP 3 -induced endothelial Ca 2+ oscillations (20, 21). …”
Section: Mitochondria In Lung Immunitymentioning
confidence: 99%